Nonstandard Neutrinos Interactions in a 331 Model with Minimum Higgs Sector - M. Medina; P. C. de Holanda (Advances in High Energy Physics)
We present a detailed analysis of a class of extensions to the SM Gauge chiral symmetry SU ( 3 ) C